The effect of the POE (Predict-Observe-Explain) learning model using a differentiation approach on student learning outcomes in the concept of temperature and heat - Oktavia, Nurlaila; Odja, Abdul Haris; Supartin, Supartin; Setiawan, Dewa Eka Gede (Universitas Muhammadiyah Mataram, 2024)
This study aims to determine the Effect of the POE (Predict-observe-Explain) Learning Model using a differentiated approach to student learning outcomes on the concepts of temperature and heat. This research was conducted at SMAN 1 Bokat. This study used an experimental method with the research design used was Pretest-Posttest Control Group Design. The sampling technique used in this study was cluster random sampling. The population in this study was all students of grade X Science 1 SMAN 1 Bokat. The sample of this study is class X as an experimental class and class X as a control class. The learning outcome instrument is an Esay test in the cognitive realm that has been validated by 3 validators. The results of this study showed that the learning outcomes of the experimental class were higher than the learning outcomes of the control class. This study aims to determine the effect of the POE (Predict-Observe-Explain) learning model with a differentiated approach on student learning outcomes in the concept of temperature and heat. This research was conducted at SMAN 1 Bokat using an experimental method with a Pretest-Posttest Control Group Design. The sampling technique used was cluster random sampling. The learning outcome instrument was an essay test in the cognitive domain validated by 3 validators. The results showed that the learning outcomes of the experimental class were higher than those of the control class. Normality tests showed that the data were normally distributed, and homogeneity tests showed that the data were homogeneous. Hypothesis testing using the t-test at a significance level of α = 0.05 indicated that t_calculated > t_table, thus H0 is rejected and H1 is accepted. It can be concluded that the POE learning model with a differentiated approach significantly affects students' learning outcomes on the concept of temperature and heat.